2007
DOI: 10.1146/annurev.genom.8.080706.092408
|View full text |Cite
|
Sign up to set email alerts
|

Mapping, Fine Mapping, and Molecular Dissection of Quantitative Trait Loci in Domestic Animals

Abstract: Artificial selection has created myriad breeds of domestic animals, each characterized by unique phenotypes pertaining to behavior, morphology, physiology, and disease. Most domestic animal populations share features with isolated founder populations, making them well suited for positional cloning. Genome sequences are now available for most domestic species, and with them a panoply of tools including high-density single-nucleotide polymorphism panels. As a result, domestic animal populations are becoming inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
11

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 112 publications
(99 reference statements)
2
102
0
11
Order By: Relevance
“…However, recent genome-wide studies involving dogs and cattle have illustrated the possibility of mapping Mendelian traits within and across breeds without creating experimental crosses. This approach, in the absence of pedigree information, takes full advantage of the phenotypic diversity found within and across different livestock breeds (Georges, 2007). By exploiting the greater number of recombination events that have occurred since breed divergence, as compared with a mapping resource pedigree, it is possible to map a phenotype to a smaller region than might be possible using a mapping pedigree.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent genome-wide studies involving dogs and cattle have illustrated the possibility of mapping Mendelian traits within and across breeds without creating experimental crosses. This approach, in the absence of pedigree information, takes full advantage of the phenotypic diversity found within and across different livestock breeds (Georges, 2007). By exploiting the greater number of recombination events that have occurred since breed divergence, as compared with a mapping resource pedigree, it is possible to map a phenotype to a smaller region than might be possible using a mapping pedigree.…”
Section: Introductionmentioning
confidence: 99%
“…In QTL detection studies, we can locate one QTL in a chromosome as a region of about 20 to 40 cM (probably harbouring 200 to 400 genes), which makes it difficult to identify the underlying gene responsible, as has been recently emphasized by Georges (2007). To refine the position several actions can be taken.…”
Section: Qtl Detection In Domestic Speciesmentioning
confidence: 99%
“…This has led to some well established and replicated associations as, for example, that between the porcine melanocortin-4 receptor (MC4R) and fatness, growth, and feed intake (Kim et al, 2000). Unfortunately, the candidate gene literature has too many non-reproducible results that made the field a bit problematic and it has been suggested that the standard used in these type of studies should be raised (Georges, 2007). At present, we have tools (microarrays) that allow us to quantify the level of expression of virtually all genes in a large number of livestock species.…”
Section: Qtl Detection In Domestic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pig, for instance, was domesticated across wide different geographic areas from Europe to Asia starting from the local wild boar populations; the Asian and European wild boar lineages diverged since at least 600 KYA (Larson et al, 2005). Thus, extreme breeds are important resources to investigate the genetic control underlying phenotypic variation (Georges, 2007).…”
Section: Introductionmentioning
confidence: 99%